O uso de jogos eletrônicos por pessoas idosas e sua relação com memória e atenção - Godoy, Anderson da Silva (2022)
To reach the aging stage, it is important to understand that the quality of life over the years will impact old age. If the human being manages to reach the stage of old age, it is normal that important changes can occur in this process, mainly in the physical and cognitive functions. Research has shown that aging is an individual process, and is affected by variables such as gender, genetic inheritance, lifestyle, natural accidents, income, education, among other factors. Electronic games are able to improve cognitive aspects in both healthy elderly people and those with cognitive decline. The main objective of this dissertation was to describe and compare the performance of elderly people who practice and do not practice electronic games in tests of attention and memory. This study is cross-sectional, descriptive and analytical. The study population consisted of elderly people who play electronic games and who do not play electronic games and the sample was recruited through social media (Facebook, Instagram and Twitter), E-mail and Whatsapp. A sociodemographic questionnaire developed by the researchers involved in the present study was applied, having the following variables: age, sex, marital status, education, housing situation, profession, physical activity, reading habits, medication use, leisure activities, habit of use of electronic games, non-electronic games, games with and/or without internet, electronic device that you use, since when you use it and the frequency of electronic games and the motivation factor. Two instruments were used with the objective of evaluating certain cognitive aspects of the elderly, namely: The Mini Mental State Examination by Telephone (Braztel-MMSE, 2011) - to assess mental status and the Portuguese Version of the Prospective Memory Questionnaire and Retrospective (PRMQ-10) - to assess prospective and retrospective memory failures. Performance on the instruments was compared between the two groups of elderly people and between sociodemographic characteristics. Ninety elderly people were evaluated, including 44 elderly people who practice electronic games and 46 elderly people who do not practice electronic games. There was no significant difference between the sociodemographic profile of the participants and the groups studied. In addition to not showing significance between the characteristics of leisure, physical activity and reading habit. There was no significant difference in the performance of the prospective and retrospective memory questionnaire PRMQ-10. As for the performance on the MMSE, the performance was significant both for elderly people who practice and for those who do not practice electronic games. The spatial orientation and language subtest was identical for both groups, as the entire sample answered the test. The registration subtest was significant for both practicing and non-practicing elderly people in the variables of reading habit, physical activity 9 ‘ and schooling. The use of electronic games did not present significant values in any of the cognitive trait assessment tests. We concluded that the level of education, physical activity and reading habits were important variables in maintaining a good cognitive level, both in elderly practitioners and non-practitioners of electronic games. It is worth mentioning the importance of studies with new scales to assess certain cognitive aspects, with a larger sample.